リュツォ・ホルム湾，プリンスオラフ海岸，及び，エンダビーランド地質調査隊報告2016-2017（JARE-58） - 外田, 智千; ホカダ, トモカズ; 馬場, 壮太郎; ババ, ソウタロウ; 亀井, 淳志; カメイ, アツシ; 北野, 一平; キタノ, イッペイ; 本吉, 洋一; モトヨシ, ヨウイチ; Nantasin, Prayath; Setiawan, Nugroho Imam; et al. (国立極地研究所, 2017)
第58次日本南極地域観測隊（JARE-58）では，2016−2017の夏期期間にリュツォ・ホルム湾，プリンスオラフ海岸，及び，エンダビーランドにおいて地質調査をおこなった．調査隊のメンバーは，日本人地質研究者4名とアジア地域（タイ，インドネシア，モンゴル）の交換科学者3名で構成され，本吉隊長が一部期間の調査に加わった．第58次夏期観測では，「しらせ」搭載の2機の大型ヘリコプター（CH101）とともに観測隊チャーターの小型ヘリコプター（AS350）1機による野外調査の支援がなされた．本稿では，観測計画を実施するための，主に設営面での計画，準備，そして行動経過について報告する． The 58th Japanese Antarctic Research Expedition (JARE-58) conducted geological field surveys in the regions of Lützow-Holm Bay, Prince Olav Coast, and Enderby Land during the 2016−2017 austral summer season. The field party consisted of four Japanese geologists and three Asian geologists (Thai, Indonesian, Mongolian), and was joined periodically by JARE-58 expedition leader, Prof. Motoyoshi. Field parties were supported throughout the summer season by a smaller secondary helicopter (AS350) in addition to two main helicopters (CH101) stationed on the icebreaker Shirase. This report summarizes field preparations and the geological work undertaken, and highlights several key points for future planning and research. departmental bulletin paper